Cardiopulmonary Resuscitation Training in Schools Following 8 Years of Mandating Legislation in Denmark: A Nationwide Survey. Issue 3 (14th March 2017) - Malta Hansen, Carolina; Zinckernagel, Line; Ersbøll, Annette Kjær; Tjørnhøj‐Thomsen, Tine; Wissenberg, Mads; Lippert, Freddy Knudsen; Weeke, Peter; Gislason, Gunnar Hilmar; Køber, Lars; Torp‐Pedersen, Christian; Folke, Fredrik
Abstract : Background: School cardiopulmonary resuscitation (CPR) training has become mandatory in many countries, but whether legislation has translated into implementation of CPR training is largely unknown. We assessed CPR training of students following 8 years of legislative mandates in Denmark. Methods and Results: A nationwide cross‐sectional survey of Danish school leadership (n=1240) and ninth‐grade homeroom teachers (n=1381) was carried out for school year 2013‐2014. Qualitative interviews and the Theory of Planned Behavior were used to construct the survey. Logistic regression models were employed to identify factors associated with completed CPR training. Information from 63.1% of eligible schools was collected: 49.3% (n=611) of leadership and 48.2% (n=665) of teachers responded. According to teachers, 28.4% (95% CI 25.0% to 32.0%) and 10.3% (95% CI 8.1% to 12.8%) of eligible classes had completed CPR and automated external defibrillator training, respectively. Among leadership, 60.2% (95% CI 56.2% to 64.1%) reported CPR training had occurred during the 3 years prior to the survey. Factors associated with completed CPR training included believing other schools were conducting training (odds ratio [OR] 9.68 [95% CI 4.65‐20.1]), awareness of mandating legislation (OR 4.19 [95% CI 2.65‐6.62]), presence of a school CPR training coordinator (OR 3.01 [95% CI 1.84‐4.92]), teacher feeling competent to conduct training (OR 2.78 [95% CI 1.74‐4.45]), and having easy access to training material (OR 2.08 [95% CI 1.57‐2.76]). Conclusions: Despite mandating legislation, school CPR training has not been successfully implemented. Completed CPR training was associated with believing other schools were conducting training, awareness of mandating legislation, presence of a school CPR training coordinator, teachers teacher feeling competent to conduct training, and having easy access to training material. Facilitating these factors may increase rates of school CPR training.